Distinct Coastal Microbiome Populations Associated With Autochthonous- and Allochthonous-Like Dissolved Organic Matter - Broman, Elias; Asmala, Eero; Carstensen, Jacob; Pinhassi, Jarone; Dopson, Mark (Frontiers in Microbiology, 2019)
Coastal zones are important transitional areas between the land and sea, where both terrestrial and phytoplankton supplied dissolved organic matter (DOM) are respired or transformed. As climate change is expected to increase river discharge and water temperatures, DOM from both allochthonous and autochthonous sources is projected to increase. As these transformations are largely regulated by bacteria, we analyzed microbial community structure data in relation to a six-month long time-series dataset of DOM characteristics from Roskilde Fjord and adjacent streams, Denmark. The results showed that the microbial community composition in the outer estuary (closer to the sea) was largely associated with salinity and nutrients, while the inner estuary formed two clusters linked to either nutrients plus allochthonous DOM or autochthonous DOM characteristics. In contrast, the microbial community composition in the streams was found to be mainly associated with allochthonous DOM characteristics. A general pattern across the land-to-sea interface was that Betaproteobacteria were strongly associated with humic-like DOM (OTUs belonging to family Comamonadaceae), while distinct populations were instead associated with nutrients or abiotic variables such as temperature (Cyanobacteria genus Synechococcus) and salinity (Actinobacteria family Microbacteriaceae). Furthermore, there was a stark shift in the relative abundance of OTUs between stream and marine stations. This indicates that as DOM travels through the land-to-sea interface, different bacterial guilds continuously degrade it.